The Place of Devotion Siting and Experiencing Divinity in Bengal-Vaishnavism - Sarbadhikary, Sukanya (University of California Press, 2015)
Hindu devotional traditions have long been recognized for their sacred geographies as well as the sensuous aspects of their devotees' experiences. Largely overlooked, however, are the subtle links between these religious expressions. Based on intensive fieldwork conducted among worshippers in Bengal's Navadvip Mayapur sacred complex, this book discusses the diverse and contrasting ways in which Bengal Vaishnava devotees experience sacred geography and divinity. Sukanya Sarbadhikary documents an extensive range of practices, which draw on the interactions of mind, body, and viscera. She shows how perspectives on religion, embodiment, affect, and space are enriched when sacred spatialities of internal and external forms are studied at once. "Sophisticated in areas of theory, The Place of Devotion teases out the subtle nuances of affect for four groups within the Gaudiya Vaishnava community, demonstrating not only how they differ, but how the differently interiorized experiences become social practices that generate strong empathic continuities." -TONY K. STEWART, Gertrude Conaway Chair in Humanities, Vanderbilt University "With exemplary skill and sensitivity, Sarbadhikary vividly documents the complex mix of emotional, aesthetic, and erotic sensibilities engaged and cultivated at one of India's most celebrated Hindu holy places. The Place of Devotion is a must read for anyone interested in Hinduism, in India, and in the implications of profound religious experiences for the understanding of self in today's modern world." -SUSAN BAYLY, University of Cambridge "Sarbadhikary makes a crucial contribution to the current anthropology of Hinduism by showing the continued vibrancy of a feminine and ecstatic mode of religious experience that has refused to surrender to the masculinist thrust of modern religious reform." -PARTHA CHATTERJEE, Professor of Anthropology and South Asian Studies, Columbia University SUKANYA SARBADHIKARY is Assistant Professor of Sociology at Presidency University, Kolkata.